HIF-1α Levels in patients receiving chemoradiotherapy for locally advanced non-small cell lung carcinoma - Afsar,Cigdem Usul (2019)
SUMMARY AIM To examine the relationship between treatment response and hypoxia-inducible factor-1 alpha (HIF-1α) levels in patients with locally advanced non-small cell lung cancer (NSCLC) who received chemoradiotherapy (CRT). METHODS Eighty patients with NSCLC were included in the study and treated at Acibadem Mehmet Ali Aydınlar University Medical Faculty. HIF-1 α levels were measured before and after CRT by the enzyme-linked immunosorbent assay (ELISA) method. RESULTS Patients’ stages were as follows; stage IIIA (65%) and stage IIIB (35%). Squamous histology was 45%, adenocarcinoma was 44%, and others were 11%. Chemotherapy and radiotherapy were given concurrently to 80 patients. Forty-five (56%) patients received cisplatin-based chemotherapy, and 35 (44%) received carboplatin-based chemotherapy. Serum HIF-1α levels (42.90 ± 10.55 pg/mL) after CRT were significantly lower than the pretreatment levels (63.10 ± 10.22 pg/mL, p<0.001) in patients with locally advanced NSCLC. CONCLUSION The results of this study revealed that serum HIF-1α levels decreased after CRT. Decrease of HIF-1α levels after the initiation of CRT may be useful for predicting the efficacy of CRT.